Trapped heart in heavily calcified pericardium - Mohd Aizuddin Zaimi; Ahmad Zuhdi Mamat; Mohamad Ziyadi Ghazali; Andee Dzulkarnaen Zakaria; Nik Amin Sahid; Firdaus Hayati (Oxford University Press, 2020)
Constrictive pericarditis is a disabling disease of the heart, which causes cardiac diastolic dysfunction. We present a case of a 44-year-old gentleman with a history of blunt chest trauma who presented with constrictive pericarditis with right-sided heart failure. Imaging studies revealed a calcified pericardium. He underwent an uneventful pericardiectomy. Calcification is common yet rare if it involves the pericardium. It normally occurs following fibrosis and adhesion which are associated with the chronicity of the disease, hence creating more challenge to the operating surgeon in the pericardiectomy procedure